2014
DOI: 10.1158/0008-5472.can-13-1296
|View full text |Cite
|
Sign up to set email alerts
|

ALCAM/CD166 Is a TGF-β–Responsive Marker and Functional Regulator of Prostate Cancer Metastasis to Bone

Abstract: The dissemination of prostate cancer to bone is a common, incurable aspect of advanced disease. Prevention and treatment of this terminal phase of prostate cancer requires improved molecular understanding of the process as well as markers indicative of molecular progression. Through biochemical analyses and loss-of-function in vivo studies we demonstrate that the cell adhesion molecule ALCAM is actively shed from metastatic prostate cancer cells by the sheddase ADAM17 in response to TGFβ. Not only is this post… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
84
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(91 citation statements)
references
References 40 publications
(51 reference statements)
6
84
1
Order By: Relevance
“…Likewise, they demonstrated that ALCAM was highly expressed on the surface of prostate stem/ progenitor and cancer initiating cells (Jiao et al, 2012). In melanoma, pancreatic-and prostate cancers, up-regulation of ALCAM is associated with invasion and metastasis (Jannie et al, 2012;Fujiwara et al, 2014;Hansen et al, 2014). Our findings support these previous studies -ALCAM up-regulated both mRNA and protein levels when the CAA cell line was induced to invasive character.…”
Section: Discussionsupporting
confidence: 89%
“…Likewise, they demonstrated that ALCAM was highly expressed on the surface of prostate stem/ progenitor and cancer initiating cells (Jiao et al, 2012). In melanoma, pancreatic-and prostate cancers, up-regulation of ALCAM is associated with invasion and metastasis (Jannie et al, 2012;Fujiwara et al, 2014;Hansen et al, 2014). Our findings support these previous studies -ALCAM up-regulated both mRNA and protein levels when the CAA cell line was induced to invasive character.…”
Section: Discussionsupporting
confidence: 89%
“…However, sustained expression of MET and CD321 in TGFβ-treated BOK overexpressing cells shows epithelial state of the cells, thus confirming the BOK role in EMT inhibition. Moreover, overexpression of BOK downregulated membrane expression of CD166/ALCAM (Figure 6), which is implicated in NSCLC cancer cells migration and invasion in vitro (41) and its reduced expression inhibited skeletal metastasis in prostate cancer in vivo (42). …”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer cells, TGF-b induces the shedding of membrane-anchored heparin-binding EGF-like growth factor and transactivates epidermal growth factor receptor (EGFR) [18]. In prostate cancer cells, TGF-b induces expression and shedding of the activated leukocyte cell adhesion molecule and enhances metastasis to bone [19]. In both case, the TGF-b-induced shedding is mediated through activation of TACE, also known as ADAM17.…”
Section: Introductionmentioning
confidence: 99%